The McGraw-Hill Encyclopedia of Space - Carpenter Scott (Mcgraw Hill Book Company, 1968)
The Rocket, Generalities, Rocket Technique, Launching Bases, Rockets of the World, The Future of the Rocket, Artificial Satellites, Satellites of the World, The World;s Scientific Satellites, Space Navigation and Electronics, Electronics, Navigation and Guidance, Man in Space, Survival in a Space Cabin, Biodynamics of Space flight, Psychological Factors, American Flights, Russian Flights, Manned Space Missions, Life in the Universe, Astronomy - Astrophysics, The Sun, The Earth, Evolution of Astronomy, The Conquest of the Moon, Present State of Knowledge, Flights to the Moon, Life in the Moon, All the Flights to the Moon, Towards Other Worlds, The Exploration of Mars, The Exploration of Venus, The Conquest of the Solar System, All Flights to the Planets, Astronautics in the World Today.